2-[18F]FDG PET/CT parameters associated with WHO/ISUP grade in clear cell renal cell carcinoma. - Zhao, Yanyan; Wu, Caixia; Li, Wei; Chen, Xueqi; Li, Ziao; Liao, Xuhe; Cui, Yonggang; Zhao, Guangyu; Liu, Meng; Fu, Zhanli (European Journal of Nuclear Medicine & Molecular Imaging, 2021)
Purpose: To explore the potential parameters from preoperative 2-[18F]FDG PET/CT that might associate with the World Health Organization/the International Society of Urological Pathology (WHO/ISUP) grade in clear cell renal cell carcinoma (ccRCC). Methods: One hundred twenty-five patients with newly diagnosed ccRCC who underwent 2-[18F]FDG PET/CT prior to surgery or biopsy were retrospectively reviewed. The metabolic parameters and imaging features obtained from 2-[18F]FDG PET/CT examinations were analyzed in combination with clinical characteristics. Univariate and multivariate logistic regression analyses were performed to identify the predictive factors of WHO/ISUP grade. Results: Metabolic parameters of primary tumor maximum standardized uptake value (SUVmax), tumor-to-liver SUV ratio (TLR), and tumor-to-kidney SUV ratio (TKR) were significantly different between any two of the four different WHO/ISUP grades, except those between the WHO/ISUP grade 3 and grade 4. The optimal cutoff values to predict high WHO/ISUP grade for SUVmax, TLR, and TKR were 4.15, 1.63, and 1.59, respectively. TLR (AUC: 0.841) was superior to TKR (AUC: 0.810) in distinguishing high and low WHO/ISUP grades (P = 0.0042). In univariate analysis, SUVmax, TLR, TKR, primary tumor size, tumor thrombus, distant metastases, and clinical symptoms could discriminate between the high and low WHO/ISUP grades (P < 0.05). In multivariate analysis, TLR (P < 0.001; OR: 1.732; 95%CI: 1.289–2.328) and tumor thrombus (P < 0.001; OR: 6.199; 95%CI: 2.499–15.375) were significant factors for differentiating WHO/ISUP grades. Conclusion: Elevated TLR (> 1.63) and presence of tumor thrombus from preoperative 2-[18F]FDG PET/CT can distinguish high WHO/ISUP grade ccRCC effectively. 2-[18F]FDG PET/CT may be a feasible method for noninvasive assessment of WHO/ISUP grade.